A new species of the genus Tetratoma Fabricius (Coleoptera, Tetratomidae) from China - Nikitsky, N.b. (Zootaxa, 2016)
A new species of tetratomid beetle, Tetratoma (s. str.) yunnanensis Nikitsky sp. nov. is described from Southern China (Yunnan). Description, colour habitus photographs and an illustration of the aedeagus are provided, and the species is compared with other members of the genus. Biogeographical observations on the species and subgenera of Tetratoma are given.